2023
DOI: 10.1039/d3sc04339h
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric materials for ultrasound imaging and therapy

Roman A. Barmin,
MirJavad Moosavifar,
Anshuman Dasgupta
et al.

Abstract: Ultrasound (US) is routinely used for diagnostic imaging and increasingly employed for therapeutic applications. Materials that act as cavitation nuclei can improve the resolution of US imaging, and facilitate therapeutic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…[ 36,37 ] Although this was a significant improvement compared to 20 kHz US for potential biocompatibility, the inherent reliance on inertial cavitation will prohibit the safe use of this system in living systems. Therefore, further research to activate DNAzymes, e.g., by stable cavitation using auxiliaries like microbubbles [ 38,39 ] will be necessary. Moreover, the reduction of tissue damage through cavitation effects mandates short sonication times.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36,37 ] Although this was a significant improvement compared to 20 kHz US for potential biocompatibility, the inherent reliance on inertial cavitation will prohibit the safe use of this system in living systems. Therefore, further research to activate DNAzymes, e.g., by stable cavitation using auxiliaries like microbubbles [ 38,39 ] will be necessary. Moreover, the reduction of tissue damage through cavitation effects mandates short sonication times.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Moreover, the MB air-filled core displays acoustic responsiveness, leading to its primary use in US contrast imaging. 26 The PBCA MB platform is biocompatible at diagnostic doses, and can be bioconjugated with targeting agents, expanding its use to molecular imaging and targeted drug delivery, among others. 24,27,28 In a previous study, we demonstrated the good loading of hydrophobic molecules with different chemical structures, namely nile red (log P value of 3.5), coumarin 6 (log P 4.9), and pyrene (log P 6.0) in PBCA MB, and their US-induced release.…”
Section: Introductionmentioning
confidence: 99%